Application of Nanomaterials in Luminescent Solar Concentrator to Reduce Re-Absorption Loss - Abdalla Ebraheem, Omer Faisal (2018)
With the high usage of electricity, environmental friendly choices became more important than ever. Hence, making Solar-electrical energy alternative is a possible solution despite being expensive but this price can be brought down when the surface area of the PV cell used is reduced which is the aim of this project. By developing Luminescent Solar Concentrator (LSC) that absorb and concentrate the light into the Photovoltaic Cell where the energy conversion takes place but in order to do that a nanomaterial should be doped into luminescent solar concentrator to bring up the best capabilities of the LSC.